Reassessing Nutritional Supplementation Program: The Impact of Maternal Vitamin B12 Levels on Feto-Maternal Outcomes - Dhume, Pranjali; Rawal, Reshu; Vadhera, Ashish; Shah, Ankur; Dey, Madhusudan; Chawla, Sunil; Goel, Suyash; Gilhotra, Simran; Sharma, Ankita (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: In India, despite the high prevalence of vitamin B12 (vit B12) deficiency, the current public health policy focuses solely on iron and folic acid supplementation as a measure to prevent anaemia. Vit B12 is an important cofactor for enzymatic reactions related to DNA synthesis, folate, and cell metabolism. While folate deficiency has been acknowledged in not only the prevention of neural tube defects and other adverse pregnancy outcomes, the effects of low vit B12 status have not been well defined. It is becoming recognized that there is a much higher prevalence of B12 deficiency than earlier suspected, and more of its effect on maternal and fetal health is being reported. The current study was planned as an observational study to correlate the effects of vit B12 deficiency with respect to various feto-maternal outcomes. STUDY DESIGN: In this prospective cohort study a total of 300 antenatal women were screened for vit B12 levels in the late first trimester and were followed up to find out co-existent folic acid deficiency, development of pregnancy complications like anemia, gestational hypertension/pre-eclampsia, fetal growth restriction (FGR), second-trimester abortions, gestational diabetes mellitus (GDM) and preterm deliveries. RESULTS: It was found that most of the women with low B12 levels were vegetarian and had co-existent folic acid deficiency. They had a statistically significant increase in the incidence of anemia, pre-eclampsia, gestational diabetes, (small for gestational age) SGA/FGR, and preterm births. CONCLUSION: The study suggests that low levels of vit B12 increase the likelihood of adverse feto-maternal outcomes. Further research involving larger sample sizes is necessary to confirm these findings and determine if vit B12 supplementation should be included in pregnancy nutritional supplements, especially in vegetarian women.